Analisis Kategori Penyebab Klaim Pending BPJS Kesehatan pada Pasien Rawat Jalan di RSUD dr. Soedirman Kebumen - Ivana, Salma; Romodon, Dion; Hakim, Agya Osadawedya; Al Ghifary, Luthfi Firdaus (Akademi Perekam dan Informasi Kesehatan Imelda, 2025)
Health insurance claims are submitted by health facilities to BPJS Health to request payment of health service costs. The process of submitting claims from RSUD Dr. Soedirman Kebumen to BPJS Kesehatan does not always run smoothly. Every month, claim files that do not meet the BPJS claim verification requirements are returned by BPJS Kesehatan to RSUD Dr. Soedirman Kebumen due to not passing verification because the submitted claim does not meet the requirements for BPJS Kesehatan claims, so BPJS needs to reconfirm with the hospital. The purpose of this research is to analyze and study the various categories of causes of delayed BPJS Health claims on outpatients at RSUD Dr. Soedirman Kebumen. The research method used in this article is descriptive qualitative with a cross sectional study design. Data collection was carried out by document review and structured interviews . The data source was obtained from the Medical Records Installation section for the period August-October 2023. The research results show that 99% (39,896) of the files passed verification and 1% (552) of the files were pending out of a total of 40,448 pending claim files submitted to BPJS Health for the period August-October 2023. There were five categories of causes of the most pending claims in the period August-October 2023, dominated by the category of re-control cases without any indication of not being guaranteed, with 123 pending claim files. Due to pending claims, the hospital's cash flow is disrupted.